Clinical report and analysis of 24 cases of multiple magnetic beads foreign body in gastrointestinal tract of children - Li, Xian-Ling; Zhang, Qin-Ming; Lu, Shou-Yan; Liu, Ting-Ting; Yao, Zi-Ming; Zhang, Wei-Ping; Chen, Ya-Jun; Chen, Long; Xie, Fang-Nan (Turkish Journal of Gastroenterology, 2020)
Background/Aims: This study aimed to analyze the data of 24 cases of multiple perforation or obstruction of the digestive tract caused by accidental ingestion of magnetic beads, to improve the understanding of its harmfulness to children and explore the best treatment. Materials and Methods: In total, 24 cases were collected and retrospectively analyzed. These patients were divided into two groups: perforation group and non-perforation group. The medical history, number of magnetic beads, white blood cell (WBC) count, and C-reactive protein (CRP) were analyzed. Results: There was no significant difference in age, gender, medical history, number of magnetic beads, and WBC count between the perforation group and non-perforation group, but there was a significant difference in CRP. After the diagnosis, 70% of the cases underwent laparotomy and perforation repair. All cases recovered smoothly after the operation, and no complications occurred during the follow-up. Conclusion: This study offers diagnosis and treatment methods for the perforation or obstruction of the digestive tract caused by accidental ingestion of magnetic beads and raises the awareness regarding the harmfulness of the presence of foreign bodies in the digestive tract.